THE ROLE OF NEW INFORMATION TECHNOLOGIES IN ALTERNATIVE RESOLUTION OF DIVORCE DISPUTES - Michał Araszkiewicz; Agata Łopatkiewicz; Adam Zienkiewicz (European Scientific Journal, ESJ, 2014)
This paper is an introductory outline to the problems of application of intelligent information technology in the process of alternative resolution of family disputes. The three layers that are relevant for this research, namely, the legal layer, the layer concerning the theory and practice of dispute resolution and the layer of information technology are discussed. The illustrative material is taken from the Polish family law, with emphasis on the so-called parenting plans: the agreements pertaining to the allocation of the parental custody after the divorce is granted. The following two negotiation support systems are compared: the Family_Winner system developed by Emilia Bellucci and John Zeleznikow and, on the other hand, the Parent Plan Support System designed by the authors of this paper.